(untitled) (Journal of Bangladesh Institute of Planners, 2016)
In achieving environmental sustainability, planning of a city or region can be more functional and implementable by using low carbon city concept. Urban Planning through land use planning and planning control can play a vital role in implementing the idea of low carbon cities, particularly during the formulation of development plans. The study focuses on the issues of carbon emission and global warming due to emission from the brick fields of Dhaka in Bangladesh. The brick manufacturing in the Greater Dhaka region produces 3.5 billion bricks per year, and it has been estimated that about 23,300 tons of particulate matter having aerodynamic diameter <2.5 μm (PM2.5), 15,500 tons of sulfur dioxide (SO2), 302,000 tons of carbon monoxide (CO), 6,000 tons of black carbon (BC) and 1.8 million_tons of carbon dioxide (CO2) are emitted annually. This paper presents a case study of brick kilns on three unions (Aminbazar, Savar and Ashulia) of Savar Upazila under Dhaka District. The study provides a review of legal aspects on brick kilns in the context of Bangladesh. Finally, some recommendations have been provided for the improvement of urban environmental management due to emission from brick kilns. JBIP, Vol. 9, 2016 (Printed in April 2018), pp. 155-170